If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2y-3-(-4y+5+(-y+2-(3y-1)+2-5))=-(y-4)
We move all terms to the left:
-2y-3-(-4y+5+(-y+2-(3y-1)+2-5))-(-(y-4))=0
We calculate terms in parentheses: -(-4y+5+(-y+2-(3y-1)+2-5)), so:
-4y+5+(-y+2-(3y-1)+2-5)
determiningTheFunctionDomain -4y+(-y+2-(3y-1)+2-5)+5
We calculate terms in parentheses: +(-y+2-(3y-1)+2-5), so:We get rid of parentheses
-y+2-(3y-1)+2-5
determiningTheFunctionDomain -y-(3y-1)+2+2-5
We add all the numbers together, and all the variables
-1y-(3y-1)-1
We get rid of parentheses
-1y-3y+1-1
We add all the numbers together, and all the variables
-4y
Back to the equation:
+(-4y)
-4y-4y+5
We add all the numbers together, and all the variables
-8y+5
Back to the equation:
-(-8y+5)
We calculate terms in parentheses: -(-(y-4)), so:We get rid of parentheses
-(y-4)
We get rid of parentheses
-y+4
We add all the numbers together, and all the variables
-1y+4
Back to the equation:
-(-1y+4)
-2y+8y+1y-5-4-3=0
We add all the numbers together, and all the variables
7y-12=0
We move all terms containing y to the left, all other terms to the right
7y=12
y=12/7
y=1+5/7
| 2=7(w+2)-4w | | 55+26×-1=80x | | 11=6x-1+6x | | -8=-5v+7(v-4) | | -11-2k=1-8k | | 11x-5(2x-1)=5(6-x)+3 | | 7c-(1/3)=(7/9) | | 7x+2x-9=2(4x+8) | | -11-2k=-1-8k | | -7(9n+8)=-31-4n | | -0.67(x+2)=0.17(x+6) | | 90+.50m=50+.60m | | 40(p-4.5)=112 | | .16x+21=x | | 4-8X=9x+20 | | 3h=7(2÷7-3÷7h)-10 | | 8x-9x=-29 | | x/4-5=6-x/4 | | 4/5-x=2 | | 2(3x+2)=x-4 | | 4-8x=9x+8 | | 6x+4x-76=38-9x | | 0.5x-3.5=0.3x-0.5 | | C/3+5=7c | | 6v-4v=6+v-5v | | 7-2(-5x-9)+2x=4(2x-1)+3(×+12) | | 24x=8x+;8 | | 2(3x-2)=(2x+4) | | 6.5(10^x)=3 | | -12-4b=4b-2b | | x2+3x-5=5x+3x=1 | | |x^2-36|=8 |